TERMOGRAFIA NA AVALIAÇÃO DA EFICÁCIA DE BLOQUEIO DO PLEXO BRAQUIAL EM CÃES - Simone Marques Caramalac (2023)
In the medical routine of performing anesthetic blocks, one of the main challenges for anesthesiologists is certifying the success of the block performed. A means of evaluating the effectiveness of locoregional blocks with high sensitivity and specificity is capable of improving pain control, since reaching the nociceptive threshold makes pain relief treatment more difficult. Thermography is a tool that is less susceptible to partiality or subjectivity in the evaluation of the effectiveness of local blocks, with the advantages of lack of contact and non-dependence of the patient's responses to stimuli. Thus, this study aimed to determine whether thermography can be used as an early and objective method in determining the effectiveness of brachial plexus block in dogs. For this, 20 dogs were used, in which 10 of them underwent brachial plexus block, using the contralateral limb as a control. In the other 10 animals, only general anesthesia and thermographic images of the limbs were performed, in order to assess whether there would be a systemic effect of local anesthetics on the temperature of the limbs. Thermographic images of the lateral, medial, cranial and caudal regions of the forelimbs and cushions were performed before the deposition of the anesthetic in the nerves. The animals were kept under general anesthesia with sevoflurane. 5 mg/kg of 1% lidocaine was used to perform the brachial plexus block, with images being taken every 2 minutes, for twenty minutes, for later evaluation of the areas of interest, which corresponded to the regions innervated by the radial and brachycephalic nerves. , musculocutaneous, ulnar, and lateral cervical root of the second thoracic vertebra, in addition to the cushions. There was no significant difference between the temperatures of the blocked limb and the contralateral limb, so thermography was not effective in predicting the effectiveness of the anesthetic block. However, from some specific moments, an increase in the temperature of the limbs was observed in both groups, in the regions innervated by the radial, brachycephalic, ulnar nerves and cushions, in addition to a reduction in body temperature, with a significant negative correlation between them. This can be attributed to vasodilation induced by general anesthetics, in addition to the inhibition of thermoprotective mechanisms (such as tremor for example), both resulting in hypothermia. In one animal, transient Horner syndrome occurred because of brachial plexus block. Thus, the vasodilation caused by the inhalational anesthetic overlapped the vasodilation induced by the local anesthetic, so that thermography was not effective to assess the effectiveness of the blockade in these conditions.